Women’s land rights realities in the ‘Rubi-Tele’ Hunting Domain, in the Democratic Republic of the Congo - Ibanda, G.; Bulonza, E.; Sabongo, P.; Amundala, N.; Mampeta, S.; Sonwa, D.J. (African Studies Centre, 2021)
Women contribute to reducing hunger and improving household food security and livelihood. However, they do not benefit from secure land rights. This study thus aimed to determine the factors that prevent women from Rubi-Tele from enjoying their rights. A 2-week survey completed by four focus groups in four villages helped us gather information that was later analysed using a socio-legal approach. All women were involved in agriculture, but they were the only workers who could not control or manage the land. They often accessed land through the family channel (96.7%), while other pathways were less used by the origin (3.3%). Although the Democratic Republic of the Congo has made enormous progress, women were unaware of these advances: thus, 70% did not know their rights. This unawareness impeded their ability to initiate strategies to claim their rights. Some women have been able to identify their difficulties. They incriminated the custom standards that favoured their male counterparts (21.7%). Additionally, begging for husband permission (28%) and poverty (20%) were cited as barriers to women’s property rights. Moreover, some women conservationists preferred the custom to formal laws, despite their advances (30%). No strategy has been initiated because women fear the society’s response.